Perbandingan Proporsi Hipertensi pada Pasien DMT2 Obesitas dan Non Obesitas di RS UKRIDA - Massie, Naomi; Dharmawan, Guntur; Winaktu, Gracia JMT (Universitas Kristen Krida Wacana, 2026)
Type 2 diabetes mellitus (T2DM) is a major global health burden with rising prevalence and complications, including hypertension as a key comorbidity that increases cardiovascular risk in both obese and non-obese patients. This study aimed to analyze differences in hypertension proportions between obese and non-obese T2DM patients at UKRIDA Hospital from January 2022 to May 2025 and to describe variations by age and gender. Using a comparative analytical cross-sectional design and total sampling, the study included 348 eligible patients. Data were analyzed using the Pearson Chi-square test, revealing a significant association between nutritional status and hypertension (p = 0.024; OR = 1.656; φ = 0.121). Obese T2DM patients were 1.6 times more likely to develop hypertension than non-obese ones, though the relationship was weak. Hypertension prevalence was similar across age (<65 and ≥65 years) and gender groups. In conclusion, hypertension was common in both obese and non-obese T2DM patients, suggesting that factors beyond obesity contribute to elevated blood pressure in this population.